Effect of 4 months of training on aerobic power, strength, and acceleration in two under-19 soccer teams - Lopez-Segovia, M.; Palao Andrés, J. M.; Gonzales-Badillo, J. J. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to assess the effect of the training executed by 2 under-19 teams from the first Spanish division on aerobic power, strength, and acceleration capacity. Two under-19 soccer teams that competed in the same league were evaluated on 2 occasions. The first evaluation (E1) was done at the beginning of the competitive period, and the second evaluation (E2) was done 16 weeks later, coinciding with the end of the first half of the regular season. The following were evaluated: lower-body strength through jump height with countermovement with and without load (CMJ/CMJ20), speed of the Smith machine bar movement in a progressive load test of full squats (FSL), acceleration capacity in 10, 20, and 30 m (T10, T20, T30, T10-20, T10-30, T20-30), and maximal aerobic speed (MAS). Team A executed complementary strength training, and training loads were determined with regard to the speed with which each player moved the bar in FSL. Between the evaluations, the training sessions of each team were recorded to assess their influence on the changes in E2. Team A significantly improved its MAS (p < 0.01) and its application of strength in the CMJ20 (p < 0.05) and FS20-30-40 (p < 0.01), while significantly worsening their acceleration capacity in all the splits (p < 0.01). Team B slightly worsened its MAS and significantly improved its application of strength in the CMJ20 (p < 0.01) and FS50-60 (p < 0.05). Its acceleration capacity improved insignificantly except for in the 20- to 30-m interval/T20-30 (p < 0.05). The present study demonstrates that the use of loads as a function of the speed of movement, without the need to determine maximum repetitions is a methodology that is adequate for the improvement of the application of strength in under-19 soccer players.